Cardiovascular preparticipation screening in young athletes. Looking through one lens - Asif, I. M.; Drezner, J. A.; O`Connor, F. G. (Sports Health: A Multidisciplinary Approach, 2017)
Cardiovascular (CV) screening in young competitive athletes is recommended by the majority of medical and sports governing organizations. There is, however, substantial controversy surrounding the most appropriate screening protocol and whether to add a resting 12-lead electrocardiogram (ECG) to the preparticipation history and physical examination. Rather than continue polarized debates and contentious discourse, the American Medical Society for Sports Medicine (AMSSM) took a unique stance and formed a task force of balanced perspectives to address the current evidence and knowledge gaps regarding preparticipation CV screening in athletes from the eye of a primary care sports medicine physician (http://www.amssm.org/Publications.html).